Emergency department length of stay and outcomes of emergency department–based intensive care unit patients - Henrique A. Puls; Nathan L. Haas; James A. Cranford; Richard P. Medlin Jr; Benjamin S. Bassin (Journal of the American College of Emergency Physicians Open)
Abstract Objective Emergency department (ED) boarding of patients who are critically ill is associated with poor outcomes. ED‐based intensive care units (ED‐ICUs) may mitigate the risks of ED boarding. We sought to analyze the impact of ED length of stay (LOS) before transfer to an ED‐ICU on patient outcomes. Methods We retrospectively analyzed adult ED patients managed in the ED‐ICU at a US medical center. Bivariate and multivariable linear regressions tested ED LOS as a predictor of inpatient ICU and hospital LOS, and separate bivariate and multivariable logistic regressions tested ED LOS as a predictor of inpatient ICU admission, 48‐hour mortality, and hospital mortality. Multivariable analyses’ covariates were age, sex, Charlson Comorbidity Index (CCI), Emergency Severity Index, and eSimplified Acute Physiology Score (eSAPS3). Results We included 5859 ED visits with subsequent care in the ED‐ICU. Median age, CCI, eSAPS3, ED LOS, and ED‐ICU LOS were 62 years (interquartile range [IQR], 48–73 years), 5 (IQR, 2–8), 46 (IQR, 36–56), 3.6 hours (IQR, 2.5–5.3 hours), and 8.5 hours (IQR, 5.3–13.4 hours), respectively, and 46.3% were women. Bivariate analyses showed negative associations of ED LOS with hospital LOS (β = −3.4; 95% confidence interval [CI], −5.9 to −1.0), inpatient ICU admission (odds ratio [OR], 0.86, 95% CI, 0.84–0.88), 48‐hour mortality (OR, 0.89; 95% CI, 0.82–0.98), and hospital mortality (OR, 0.89; 95% CI, 0.85–0.92), but no association with inpatient ICU LOS. Multivariable analyses showed a negative association of ED LOS with inpatient ICU admission (OR, 0.91; 95% CI, 0.88–0.93), but no associations with other outcomes. Conclusions We observed no significant associations between ED LOS before ED‐ICU transfer and worsened outcomes, suggesting an ED‐ICU may mitigate the risks of ED boarding of patients who are critically ill.